Daidzein alleviates neuronal damage and oxidative stress via GSK3β/Nrf2 pathway in mice. (May 2022) - Wang, Xuerui; Yin, Zequn; Meng, Xianshe; Yang, Daigang; Meng, Huawen; Liao, Chenzhong; Wei, Lingling; Chen, Yuanli; Yang, Xiaoxiao; Han, Jihong; Duan, Yajun; Zhang, Shuang
Graphical abstract: DAI can improve the development of Parkinson's disease in MPTP-injected model mice by following actions: 1) it can promote the entry of Nrf2 into the nucleus by inhibiting the activity of GSK3β, and then inhibit the oxidative stress response in neurons; 2) it can suppress the expression of MAO-B and SCNA, and promote the expression of TH, thus improve the apoptosis of DA neurons and behavioral disorders in MPTP-injected mice. Highlights: Daidzein ameliorated apoptosis in LPS-induced BV2 cells. Daidzein ameliorated intracellular ROS levels and antioxidant capacity. The protection was associated with the activation of GSK3β/Nrf2/ARE pathway. Daidzein prevented mobility disorders in MPTP-induced mice. Daidzein promoted the antioxidant capacity in mice brain through GSK3β/Nrf2 pathway. Abstract: Parkinson's disease (PD) is the most common neurodegenerative disease. Daidzein (DAI) is one of the most commonly ingested phytoestrogens with anti-oxidant properties. However, the effects of DAI on oxidative stress in PD has not been reported. In this study, we used 1-methyl-4-phenyl-1, 2, 3, 6-tetrahydropyridine (MPTP) for intraperitoneal injection of C57/BL6J mice for continuous 7 days to simulate the pathological process of PD. Results showed that DAI improved the movement disorders and reduced the loss of DA neurons in the brain of mice induced by MPTP. Mechanistically, in vitro, DAI pretreatment up-regulated the expression of Nrf2 and its downstream SOD1 and SOD2 by inhibiting the activity of GSK3β in lipopolysaccharide-stimulated BV2 cells; in vivo, DAI pretreatment attenuated GSK3β activity, increased the expression of Nrf2 and downstream anti-oxidants SOD1, SOD2 and CAT. Our data demonstrated that DAI restrains oxidative stress in PD by regulating the GSK3β/Nrf2 pathway.